Macro prudential supervision in the open economy, and the role of central banks in emerging markets - Joshua Aizenman (University of California, Economics Department, 2010)
In this paper we explore lessons from the global liquidity crisis pertaining to the prudential supervision role of central bank in an open economy. The narrow view of the role of central banks has been seriously challenged by the global liquidity crisis of 2008-9. The crisis validates central banks' responsibility for prudential regulations and policies aimed at reducing susceptibility of economies to crises, and the need for external debt management policy in emerging markets. Hoarding international reserves (IR) is a potent self-insurance mechanism. However, it is associated with relatively high costs and is also less efficient in absence of assertive external debt management policies. In the presence of congestion externalities associated with deleveraging, optimal external borrowing-tax-cum-IR-hoarding-subsidy reduces the cost as well as the scale of hoarding IR.
Keywords: F15; F31; F43; 330; prudential supervision; deleveraging; congestion externalities; external debt management; Kapitalmobilität; Auslandsverschuldung; Zahlungsbilanzungleichgewicht; Finanzmarktkrise; Geldpolitik; Schwellenländer